The expression of stemness markers in organoids according to histological subtypes of gastric cancer - Yie-Ri Yoo; Kyoungyun Jeong; Jaeun Yoo; Hyun Myong Kim; Ji-Yeon Shin; Min Kyu Kang; Kyoyoung Park; Sa-Hong Kim; Chungyoon Kim; Jeesun Kim; Young Suk Park; Seong-Ho Kong; et al. (Korean Journal of Clinical Oncology, 2026)
Purpose: Gastric cancer is a heterogeneous disease in which cancer stem cell-associated properties may contribute to tumor heterogeneity and progression. This study aimed to establish paired normal and tumor gastric organoids, characterize stemness-related gene expression, and explore its association with organoid formation.Methods: Normal and tumor tissues were obtained from 12 patients with advanced gastric cancer. A total of 28 independent organoid cultures were established from 24 tissue specimens (12 normal and 12 tumor), with selected serial strip specimens divided into segments and cultured independently. Expression of stemness-associated markers (AQP5, CD44, ALDH1A, STMN1, and SOX2) was evaluated by quantitative real-time polymerase chain reaction and compared according to tissue origin, histological subtype, and organoid formation status.Results: Normal organoids tended to exhibit higher CD44 expression, whereas tumor-derived organoids showed relatively higher ALDH1A expression, although these differences were not statistically significant. Margin-derived normal organoids tended to show higher expression of multiple stemness-associated markers than those derived from tissue adjacent to tumors. Diffuse-type organoids tended to show higher CD44 expression, whereas AQP5, ALDH1A, STMN1, and SOX2 tended to be higher in intestinal-type organoids. Organoid-forming cultures consistently showed higher stemness-marker expression than non-forming cultures, particularly among tumor-derived organoids.Conclusion: Stemness-associated gene expression varied according to tissue origin, histological subtype, and organoid formation status. Higher stemness-marker expression in organoid-forming cultures suggests a potential association between stemness-related programs and organoid-forming capacity.